Along came a spidey! - Simone, Gail; Lethcoe, Jason; Gurihiru (Edina, Minn. Spotlight, 2006)
Gus, Peter Parker's cousin, pretends to be Spider-Man and wins the class race, but loses to his sister during a rematch because she cheats.
"Marvel age"--Cover.
Revision of the Feb. 2004 issue of the comic book Marvelous adventures of Gus Beezer and Spider-Man.
94220
Keywords: Spider-Man (Fictitious character); Heroes; Good and evil; Comic books, strips, etc; Graphic novels; Graphic novels; Superhero comic books, strips, etc